Bayesian estimation of the size of a population - Michael Höhle; Leonhard Held (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2006)
We consider the following problem: estimate the size of a population marked with serial numbers after only a sample of the serial numbers has been observed. Its simplicity in formulation and the inviting possibilities of application make this estimation well suited for an undergraduate level probability course. Our contribution consists in a Bayesian treatment of the problem. For an improper uniform prior distribution, we show that the posterior mean and variance have nice closed form expressions and we demonstrate how to compute highest posterior density intervals. Maple and R code is provided on the authors' web-page to allow students to verify the theoretical results and experiment with data.
urn:nbn:de:bvb:19-epub-2094-7
Keywords: 519; Bayesian inference; Combinatorics; Hypergeometric functions; Maple; R